Excitation Transfer Engineering in Ce‐Doped Oxide Crystalline Scintillators by Codoping with Alkali‐Earth Ions. Issue 7 (22nd February 2018) - Auffray, Etiennette; Augulis, Ramūnas; Fedorov, Andrei; Dosovitskiy, Georgy; Grigorjeva, Larisa; Gulbinas, Vidmantas; Koschan, Merry; Lucchini, Marco; Melcher, Charles; Nargelas, Saulius; Tamulaitis, Gintautas; Vaitkevičius, Augustas; et al.
Abstract : Time‐resolved spectroscopic study of the photoluminescence response to femtosecond pulse excitation and free carrier absorption at different wavelengths, thermally stimulated luminescence measurements and investigation of differential absorption are applied to amend the available data on excitation transfer in GAGG:Ce scintillators, and an electronic energy‐level diagram in this single crystal is suggested to explain the influence of codoping with divalent Mg on luminescence kinetics and light yield. The conclusions are generalized by comparison of the influence of aliovalent doping in garnets (GAGG:Ce) and oxyorthosilicates (LSO:Ce and YSO:Ce). In both cases, the codoping facilitates the energy transfer to radiative Ce 3+ centers, while the light yield is increased in the LYSO:Ce system but reduced in GAGG:Ce. Abstract : Detailed study of the GAGG and LSO crystals by pump‐probe method is performed for first time. The dependence of free carrier absorption is found to be not following the typical spectrum due to free holes absorption by the ground level of gadolinium ions, localized by 1 eV lower than the top of the valence band. Similar features are not observed in lutetium‐based crystals.